Ectopic Pancreas in the Stomach Successfully Resected by Endoscopic Submucosal Dissection - Masaya Iwamuro; Takao Tsuzuki; Shogen Ohya; Hiroyuki Okada; Takehiro Tanaka; Keisuke Hori; Masahide Kita; Seiji Kawano; Yoshiro Kawahara; Kazuhide Yamamoto (Case Reports in Medicine)
A 32-year-old Japanese man presented with a gastric submucosal tumor. Esophagogastroduodenoscopy showed a sessile submucosal tumor measuring approximately 10 mm in diameter on the greater curvature of the gastric antrum. Endoscopic ultrasonography examination revealed a solid tumor with a diameter of 11.8 mm, which was located in the deep mucosal and submucosal layers. The internal echogenicity was homogenous and hypoechoic. Biopsy examinations were performed twice but were not diagnostic since only the intact mucosal layer was obtained. The patient was subsequently diagnosed with ectopic pancreas in the stomach by endoscopic submucosal dissection (ESD). This case underscores the usefulness of the ESD technique for the pathological diagnosis of gastric submucosal tumors.